Potensi Desa Wisata Nagari Mandeh sebagai Destinasi Unggulan - Iftita Rahmi Efendi Efendi (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2022)
The potential of Nagari Mandeh Tourism Village as a leading destination Nagari Mandeh is a tourist village located in Pesisir Selatan Regency, West Sumatra Province. This study aims to explore the potential contained in Nagari Mandeh. Using the mixed method, the researcher obtained qualitative data through observation, interviews, and documentation, which were then analyzed by data reduction, data presentation and conclusion drawing. Quantitative data was obtained through surveys and analyzed descriptively. The results of the study indicate that the Nagari Mandeh Tourism Village has enormous potential to become a leading destination, assessed from five tourist destination indicators, as well as the general response of the community who gave a very good assessment of the tourism potential of Nagari Mandeh